بناء مقياس جودة الحياة للطلبة الجامعيين - سليمان، محمد المتوكل على الله حسن (جامعة حلوان - كلية التربية الرياضية للبنين, 2017)
يهدف هذا البحث إلى بناء مقياس لجودة الحياة للطلبة الجامعين من خلال الابعاد التالية: 1. البعد الأول: الصحة العامة. 2. البعد الثاني: الصحة النفسية. 3. البعد الثالث: التعليم والدراسة. 4. البعد الرابع: العلاقات الاجتماعية والاسرية. 5. البعد الخامس: إدارة الوقت. استخدم الباحث المنهج الوصفي والمنهج الاحصائي لمناسبتهما لتحقيق متطلبات هذا البحث. بلغ حجم العينة (450) طالب من طلبة كلية التربية الرياضية للبنين من الفرق الأربعة بالكلية وتم اختيارهم بالطريقة الطبقية العشوائية. وتوصل الباحث لبناء مقياس جودة الحياة للطلبة الجامعيين والمكون من (5) أبعاد ويضم (41) عبارة مستخلصة من التحليل العاملي وهي على الترتيب: • البعد الأول: الصحة العامة ويتضمن (8) عبارات جمعيها في اتجاه البعد. • البعد الثاني: الصحة النفسية ويتضمن (8) عبارة جمعيها في اتجاه البعد. • البعد الثالث: التعليم والدراسة ويتضمن (10) عبارات جمعيها في اتجاه البعد. • البعد الرابع: العلاقات الاجتماعية والاسرية ويتضمن (10) عبارات جمعيها في اتجاه البعد. • البعد الخامس: إدارة الوقت ويتضمن (5) عبارة جمعيها في اتجاه البعد. يتميز المقياس بمعاملات صدق وثبات عال ويمكن الاعتماد عليه كمقياس مقنن لإمكانية التعرف على مستوي جودة الحياة للطالب الجامعي
The aim of this research is to build a quality of life standard for university students through the following dimensions: 1- The first dimension: public health. 2 - the second dimension: mental health. 3 - the third dimension: education and study 4 - the fourth dimension: social and family relations. 5- The fifth dimension: time management. The researcher used the descriptive approach and the statistical method to suit them to achieve the requirements of this research. The sample size (450) students from the Faculty of Physical Education for boys from the four teams in the college and were selected in a random class method. The researcher obtained the construction of a quality-of-life measure for university students consisting of (5) dimensions and includes (41) words extracted from the general analysis, respectively: • The first dimension: public health and contains (8) phrases grouped in the direction of dimension. • The second dimension: mental health and includes (8) the words of the group in the direction of dimension. • The third dimension: education and study and contains (10) phrases grouped in the direction of dimension. • The fourth dimension: social and family relations and contains (10) phrases of the group in the direction of dimension. • The fifth dimension: time management and contains (5) the words of the group in the direction of dimension. The standard is characterized by high accuracy and reliability, and can be used as a standard measure for the possibility of identifying the quality of life of the university student
Keywords: علم النفس الاجتماعي -- الاختبارات النفسية -- جودة الحياة -- الصحة النفسية -- طلبة الجامعات